Yarı simetrik ftalosiyanin ve komplekslerinin sentezi - Dabak, Salih (Fen Bilimleri Enstitüsü, 1996)
20. yüzyılın başlarında bulunan ftalosiyaninler uzun yıllar pigment ve boyar madde olarak kullanılmışlardır. Ftalosiyaninlerin, periferal pozisyonlarına taç eter, monoaza taç eter, tetraaza ve tetratiya gibi makro halkalar ve diğer hacimli substitüentler takılmasıyla organik çözücülerde çözünür hale getirilmesi, kimyasal ve fiziksel özelliklerinde büyük değişiklikleri netice vermiştir. Ftalosiyaninler, bu nedenle son zamanlarda geniş uygulama alanı bulmuşlardır., Bu çalışmada, 6-nitro-l,3,3-triklorizoindolin ve iki farklı iminoizoindolin kullanılarak iki ayrı ftalosiyanin sentezi gerçekleştirilmiştir. 2:2 katılma şeklindeki bu kondenzasyon reaksiyonda baz olarak trietilamin ve sodyum metoksit, indirgen olarakta hidrokinon kullanılmıştır. Çalışmanın birinci bölümünde 6-nitro-l,3,3-triklorizoindolin ve 1,3- dihidro-l,3-diimino-6-(n-dodesilsulfanil)iminoizoindolin kullanılarak iki nitro ve iki dodesilsulfanil grup içeren, çapraz substitüe ftalosiyanin sentezlenmiştir. Nitro gruplarının amine indirgenmesi ve ferrosenil aldehit ile kondenzasyon reaksiyonunun gerçekleştirilmesi, yeni tip ftalosiyanini netice vermiştir. Ayrıca nitro gruplu ftalosiyaninin nikel, kobalt ve çinko kompleksleri de sentezlenmiştir. Çalışmanın ikinci bölümünde ise 6-nitro-l,3,3-triklorizoindolin ve 1,3- dihidro-l,3-diimino-6-( 2-dimetilaminoetilsulfanil ) iminoizoindolin kullanılarak yine çapraz substitüe farklı bir ftalosiyanin sentezlenmiştir. Nitro grupları amine indirgenen ftalosiyanin tiyofosgen ile reaksiyona tabi tutulmuştur. Elde edilen, izotiyosiyanat gruplu yeni ürün fotodinamik terapide kullanılır hale getirilmiştir. Elde edilen yeni maddelerin yapılan, elementel analiz, İR, NMR, UV/Vis ve kütle spektrometresi ile aydınlatılmıştır.

The first synthesis of a phthalocyanine was recorded in 1907 when Braun and Tscherniac heated o-cyanobenzamide at high temperature. The structure of this metal-free, unsubstituted phthalocyanine was determined only about a quarter of century later by the comprehensive researches of Linstead and x-ray diffraction analyses of Robertson, while examining both metal-free phthalocyanine and metallohthalocyanines. Phthalocyanines and related macrocycles have found increasing interest as conductors and photoconductors, in photovoltaic and photoelectrochemical devices, as catalsts and photocatalysts and in the photodynamic therapy (PDT) of cancer. Unsubstituted and simetrically tetra- or octasubstituted phthalocyanines have been employed for these investigations. Recently, monosubstituted phthalocyanines have attracted attention in the field of nonlineer optics, liquid crystalline properties, and thin film formation. Monofunctional phthalocyanines with one reactive functional group have the advantage of polymer binding without the disadvantage of crosslinking reactions, and they form, after binding to biomolecules like monoclonal antibodies, an interesting new group of photosensitizers for the photodynamic therapy of cancer (PDT). Therefore, it is necessary to find pathways for the synthesis of mono substituted phthalocyanines. While symmetrical phthalocyanines are easily available by tetramerization of substituted 1,2-benzenedicarbonitriles, the synthesis of pure unsymmetrically substituted phthalocyanines remains a difficult problem. The simplest and the most frequently used way is the statistical tetramerization of two different substituted 1,2-benzene dicarbonitriles, always resulting in a mixture of different substituted phthalocyanines. Another way uses the polymer-supported route. In addition to a several step procedure, this route has the main disadvantage that only low amounts can be obtained due to the low capacity of the polymeric carrier. At the beginning of this decade a new method, the ring enlargement reaction of subphthalocyanines, was described as a very promising route for the preparation of unsymmetrically substituted phthalocyanines. Reaction of chloro [7,12;14,19-diimino-21,5-nitrilo-5H-tribenzo-[ h,c,m ][ 1,16,1 ]triazacyclopenta decinato-(2-)-N22,N23,N24]-boron (chloro- SubPc) with substituted 1,3-diisoimino- vu indolenines resulted in monosubstituted metal-free phthalocyanines without formation of unsubstituted, di-, tri-, and tetrasubstituted phthalocyanines. Chloro-SubPc was described first by Meller and Ossko in 1971 by trimerization of 1,2-benzenedicarbonitrile in the presence of BCI3. Tris-(1,1- dimethylethyl)- and hexakis(hexylthio)-substituted subphthalocyanines are also described. Although crossed condensation of 1,3-diisoiminoindolenine derivate with 1,3,3-trichloroisoindolenine has been reported as an interesting method to obtain phthalocyanines substituted with two different groups, no further evidence for the application of this method has been encountered. In the present work soluble phthalocyanines peripherally substituted with two amines and two alkylsulfanyl groups crosswise has been synthesized and their reactivity has been examplified. In the first part of this work crosswise substituted phthalocyanines with two nitro and two dodecylsulfanyl-groups has been synthesized by 2:2 condensation of 1,3-dihydro- 1,3-diimino-6-(n-dodecylsulfanyl)iminoiso~ indolenine with 6-nitro-l,3,3-trichloroisoindolenine in the presence of sodium methoxide, hydroquinone and triethylamine. The synthesis of the crosswise disubstituted phthalocyanines 48-53 is shown in the Scheme 1. The starting point for both of the precursors is 4-nitro- phthalimide. It is converted into 4-nitro-phthalonitrile and subsequently nucleophilic displacement of nitro group with n-dodecylmercaptane results with 4-(n-dodecylsulfanyl)-phthalonitrile 44, which is reacted with ammonia in the presence of sodium methoxide to obtain the iminoisoindolenine derivative 45 as the first precursor. The second precursor, namely 6-nitro-l,3,3- trichloroisoindolenine 43, is prepared by chlorination of 4-nitro-phthalimide with PCI5 in o-dichlorobenzene. Cyclotetramerization of these two reactants in 2:2 ratio is accomplished in THF in the presence of triethylamine and sodium methoxide as the bases and hydroquinone as the reductant. An interesting point to be noted about the above sequence concerns the reductive coupling of chloro compound 43 with the iminoisoindolenine derivate 45. Reproducible yields of the phthalocyanines could not be obtained unless these acid acceptor and hydrogen donor are present. The assignment of the product to 2:2 combination of the reactants was made based on the fact that elemental analysis and mass spectral results confirm the proposed structure. Also the high solubility of the pc 48 can be taken as an indication of 2:2 combination of the precursors while phthalocyanines with four nitro-substituents are extremely insoluble and the solubility of a phthalocyanine product with three nitro groups on the periphery cannot be sufficiently high even one dodecylsulfanyl-group is present. With the desired anhydrous metal salts in hand, it became possible to convert the metal-free phthalocyanine 48 into metallo-derivatives. For these V1U purpose, chlorides of Ni(II) and Co(II) or acetate of Zn(II) have been used in a high boiling solvent ( e.g. quinoline ) to prepare the metallo-phthalocyanines 49- 51. After purification, the yields of these metallation reactions are found to be rather low for 49 and 50, but sufficiently high in the case of Zn(II) derivative 51. Peripheral nitro-substituents on the phthalocyanine core offer a number of possibilities to obtain reactive binding sites; reduction to amine has been carried out as an example. For this purpose, sodium sulfide is preferred as the reductant as in the case of tetranitro-substituted phthalocyanines. In order to demonstrate the reactivity of amino groups in diamino-didodecylsulfanyl phthalocyanine 52, its condensation with ferrocenylaldehyde was carried out to obtain a new phthalocyanine with two ferrocenylimino substituents together with two dodecylsulfanyl units. In addition to the elemental analysis results, the outcome of mass spectral analysis is critical in determining whether the ratio of the two precursors are 2:2 after cyclotetramerization reaction. The molecular ion peak at m/z = 1005 obtained by DCI technique for the metal-free phthalocyanine 48 provides a strong evidence for 2:2 condensation of the precursors. The fragment ion peaks also confirm the proposed structures. The metallo-phthalocyanines give reproducible mass spectra only by using FAB technique and here we observe the M + MNBA (m-nitrobenzyl alcohol, matrix) peak instead of molecular ions in 50 and 51 at m/z =1217 and 1223, respectively. The metal-free phthalocyanine 50 obtained by reduction of 48 gives the M peak at m/z = 945.2 by FAB method. The ^-NMR data of the metal-free phthalocyanine 48 shows the typical shielding of inner core protons as a broad band around 5 = -10.27 ppm. These protons could not be observed for compound 52. Chemical shifts due to the alkyl protons are the dominating signals in the spectra of 48, 49, 51 and 52. The presence of positional isomers due to the singly substituted benzo units leads to broad signals for peripheral aromatic protons. Also aggregation of phthalocyanine molecules in the concentrations used for NMR measurements might cause the broadening of the aromatic signals. The UV-Vis spectra of the metal-free phthalocyanines 48, 52 and 53 are shown in Fig. 5.9. The splitted Q band absorption is present in the case of 48 with a small distortion, but the consequence of changing two nitro-substituents 48 to two amino groups 52 is evident. Although there is only a very small shift on the absorption maxima, the intensity of higher energy side of Q band has decreased, while the lower energy side has increased. When two bulky ferrocenylimino units are bound on the periphery of metal-free pc 53, the Q band is no longer splitted and it appears to have three maxima of the same intensity at 712, 684 and 654 nm. For the metallo-pc 49 and 50, the expected absorption appears around 670 nm in chloroform with an intence shoulder on its higher energy side. In the case of Zn-pc 51 another intense absorption at 709 nm is observed additionally. The d.c. conductivities as thin films in air and in vacuum of the novel pes described in the present work are given in Table.5.3. The a-values are at the lower edge of the semiconductive range for all the pes except 52. A difference of IX order three is encountered in the latter. Although one might expect this increase in air to be a result of hygroscopic nature of the amino-substituents in 52, it has been proved not to be the case by comparable values obtained in vacuum. 44 CN NH3(g)| MeOH CH3PH2)1jS^/vvll 45 NH S(CH2)11CH3 45 M 48-53 Scheme 1. Synthesis of the phtalocyanines 48-53. In the second part of this work crosswise disubstituted metal-free-pcs carrying two trimethylaminoethylsulfanyl and two amino-groups on peripheral positions has been synthesized by 2:2 condensation of l,3-dihydro-l,3-diimino-6- (2-dimethylamino ethylsulfanyl)iminoisoindolenine 47 and 6-nitro- 1,3,3- trichloroisoindolenine 43 in presence of triethylamine, sodium methoxide and hydroquinone. The required precursors to crosswise substituted pes 54-57 are 1,3- dihydro- 1,3-diimino-6-(2-dimethylaminoethylsulfanyl)iminoisoindolenine 47 and 6-nitro- 1,3,3-trichloro-isoindolenine 43. Starting from 4-nitro-phthalonitrile, displacement of the nitro group with the -SH function of dimethylaminoethanethiol gave the phthalonitrile derivate 46 as reported earlier. It was converted into the iminoisoindole compound 47 by treatment with ammonia in the presence of sodium methoxide. 43 was prepared by chlorination of 4-nitrophthalimide with PCU in o-dichlorobenzene as given in the literature. The crosswise substituted pc 54 was prepared from the condensation of 47 and 43 in 2:2 ratio in the presence triethylamine, sodium methoxide and hydroquinone (Scheme 2.). Here triethylamine was mainly used to bind HC1 formed during the condensation of 47 and 43 and sodium methoxide and hydroquinone were necessary for pc formation 54. Further efforts to prepare metallo-pc derivatives of 54 were unsuccessful. Desired compounds could be obtained neither by carrying out the condensation of 47 and 43 in the presence of a metal salt (NİCI2 or CuCl) nor inserting the metal ion into the metal-free pc 54. In order to convert 54 into a water-soluble derivative, quaternarization with dimethyl sulfate in chloroform by refluxing for two hours was sufficient. Reduction of nitro group to amine was carried out at this step. Although sodium sulfide has been used to reduce the peripheral nitro-substituents into amines on number one of nitro-pes, in the present case reproducible results could be obtained by using Raney-nickel catalysts with hydrazine hydrate. The crytical point in characterizing the new pes 54-57 İs to verify the condensation of two precursors 47 and 43 in 2:2 ratio. In addition to the elemental analysis results, mass spectra will be definitive. Unfortunately, we could not observe the molecular ion peaks for 54 and 55, although a number of ionization methods have been employed. However, the molecular ion peak at m/z 1003 has been found for 56 together with some reasonable fragments ion by CI technique. Since 56 is the last step among the three phthalocyanines 54-56, it might be accepted as a confirmation of the proposed structures for the first two compounds. XH-NMR spectra of the new phthalocyanines 54-56 in deutorated DMSO give rather broad peaks both as a consequence of aggregation of pc units and the presence of isomers resulting from the position of substituents with respect to each other; so it is difficult to differentiate between distinct protons. However, the ratio of aromatic to aliphatic protons appear to show that benzo groups with two different substituents are present in 2:2 ratio. Also the broad absorption around XI 6.6 ppm in 56 can be easily ascribed to -NH2 groups while it disappears by D20 exchange. The inner core protons expected to appear in the strong field could be observed only in the case of 54 when deuterated chloroform is used as the solvent. The IR spectra of the pes indicates the presence of nitro groups by stretching vibrations at 1520 and 1340 cm'1 for 54 and 55. After reduction, symmetric and asymmetric stretching vibrations of amino groups in 56 appear at 3420 and 3340 cm"1 as expected. The visible absorption spectra of pes 54-57 shown in Table 5.3 differs in some ways from other reported pc derivatives. The splitted Q band absorption expected for these metal-free derivatives is not present and we have a shoulder at higher energy side in organic solvents (e.g. CHCI3, DMSO). Especially for the quaternarized pes 55, 56 and 57 which are also very soluble in water, Q band absorptions are affected extremely by the nature of the solvent ( Fig. 5.12 ). In an aprotic polar solvent (DMSO), the shift of Q bands from nitro-pc 55 to amino-pc 56 is 24 nm as expected (Table 5.3). In water, however, Q bands of both compounds show a blue shift to around 630 nm and the intensities are also lowered. Aggregation of pc units to form dimers, trimers, etc. in water is the main reason for these shifts in the spectra. The d.c. conductivities as thin films in air and in vacuum for the crosswise disubstituted pes 54-57 are given in Table 5.4. These values correspond to the semiconductive materials as encountered in number substituted pc derivatives. No appreciable difference between the values measured in air and in vacuum might be noted for 54 and 55, but after reduction of nitro groups to amine in 56 a distinct difference of the order 106 was observed between the two measurements. Similar enhancement of conductivity in air was also encountered for another pc with alkylsulfanyl- and amine- substituents 52. In conclusion, we have synthesized novel species of water soluble pes which are substituted crosswise with two reactive groups. It is expected that these compounds will be important in combining these photoactive groups with biological substrates. xu piaWNCHjC^&^^^^CN MeOWNH3 46 47 + 1)(CH3)3N/THF 'q 3 CHsONlftfrdRxpAiOTO."64-67 43 Scheme 2. Synthesis of the phthalocyanines 54-57.
Tez (Doktora)--İTÜ Fen Bil. Enst., 1996
Thesis (Ph.D.) -- İstanbul Technical University, Institute of Science and Technology, 1996
Keywords: Ftalosiyaninler; Phthalocyanines